Saving sickly children : the tuberculosis preventorium in American life, 1909-1970 - Connolly, Cynthia A. (Cynthia Anne) (Critical issues in health and medicine., 2008)
Known as "The Great Killer" and "The White Plague," few diseases influenced American life as much as tuberculosis. Sufferers migrated to mountain or desert climates believed to ameliorate symptoms. Architects designed homes with sleeping porches and verandas so sufferers could spend time in the open air. The disease even developed its own consumer culture complete with invalid beds, spittoons, sputum collection devices, and disinfectants. The "preventorium," an institution designed to protect children from the ravages of the disease, emerged in this era of Progres.